A gestão de conflitos dos usos da água em Brotas/SP sob a perspectiva do turismo e da sustentabilidade - Ribeiro, Roberta Dias de Moraes (2023)
The city of Brotas, located in the interior of São Paulo, due to the fact that it has its own water resources for bathing, vegetation and natural landscapes (receiving the title of Estancia Turística Paulista), is recognized as the national capital of adventure tourism, being a national reference in ecotourism. It is an important municipality for tourism activity in the country, as well as relevant for research that addresses tourism in natural areas and the conflicts of its management, since Brotas has its economy based predominantly on the agricultural area, directly impacting on its water resources, with conflicts of interest to meet the diversity of demands for its economic activities. Thus, the objective of the research is to analyze the conflicts of water use in Brotas/SP, from the perspective of the links between tourism and sustainability. To this end, a bibliographic research was carried out on the themes on: Brotas/SP; tourism in aquatic environments; agricultural activity and its impacts. In addition, structured interviews were conducted with the municipal government, managers, social representatives and with the tourist companies of the municipality, seeking to understand how conflict management can help minimize the negative impacts derived from tourism, as well as corroborate so that the management of municipal tourism moves in the direction of sustainable development.on water resources; management of water use conflicts, making a state of the art of existing publications. It was identified that discussions about the conflicts over the use of water in Brotas are being documented in the minutes of the CBH-TJ, evidencing the need to outline actions, programs and projects aimed at resolving these conflicts, since the conflict management strategies that currently exist in Brotas are based on the competition strategy. It was concluded that conflict management is a tool that seeks to assist in problem solving, bring together the people involved through communication, and meet the demands of all actors involved so that all are contemplated. However, to adhere to this tool in Brotas it is necessary that there is willingness, interest, availability and be open to negotiation and dialogue. There also needs to be a mediator who has the skills to diagnose the nature of the conflict; getting involved in the conflict; listen and solve the problem.